Preference to Local Food vs. Preference to "National" and Regional Food. Issue 2 (17th February 2018) - Pícha, Kamil; Navrátil, Josef; Švec, Roman
ABSTRACT: In the environment of globalisation and progressive liberalisation of the market, many small local producers were excluded from the market as uncompetitive to the producers realising scale economy due to their presence in large global market and being able to meet requirements of large retailers' chains. As there is growing consumers' interest to recover their identity, those of the local cultures and traditional values, there is a new chance for those small local producers. The problems of locally produced food recently awakened interest and aroused many discussions of practitioners and scholars as well. The aim of the presented study has been to test the parameters that influenced preferences among food product branded as national, regional, or local product. Presented models identified several consumers' attitudes and feelings that are the main predictors of the relation between consumers' preferences for local food and the preferences for national or regional food. Food made by local producers is perceived by consumers as being of higher quality and better complying with their habits and requirements than "regional" or "national" food products.